Transformer less 1Î¦ Inverter for Grid-Connected PV Systems with an Optimized Control - Baldwin Immanuel, T; Muthukumar, P; Gnanavel, C; Rajavelan, M; Marimuthu, M (International Journal of Engineering and Technology, 2018)
This paper investigates the transformerless single-phase inverter incorporates with the photovoltaic system along with the support of grid voltage. Solar Energy is a Non-Conventional Energy source which is mandatory for power generation due to their immeasurable parade and green pleasant nature. One-cycle control (OCC), Ruggedness and consistency which makes the interfacing with the grid easily. For grid interfacing, the inverter circuit does not need phase locked loop facility and are gradually being working for such solicitations. The strategy of the OCC inverter of one stage for solar PV applications is supported by means of a Sinusoidal Pulse Width Modulation to enhance inverter enactment at both low and high insolation levels. These factors allows the plan of a MPPT along P&O controller that pointedly progresses inverter playacting. Though, the OCC-based structures testified previous sensing of the grid voltage which slightly equalizers the strength of its characteristics, In order to dazed the restriction of prior researches, an One Cycle Control based grid-connected one-stage PV system is suggested. The sustainability of the suggested scheme is inveterate by performance simulation justification.